Oral Traditions and Human Development in Africa: Lessons from the Ibibio- -Speaking People of Nigeria - Ibanga, Edidiong C. (Africana Studia, 2022)
This paper examines the concept of oral traditions (oral literature) in Africa, and its relevance to human development. It draws attention to the richness of indigenous knowledge contained in oral literature and demonstrates how the characters of individuals within a community can be molded by the values embedded in oral literature. The paper argues that the issue with development, especially in Africa, is that it is often seen only from the viewpoint of industrialization or productivity, thereby neglecting the need to transform the human mind. Oral literature is at the center of human development because, like the function of literature itself, it promotes ethically driven actions, by educating on what ought to be and not just what is. It concludes that any discussion on development and social change in Africa, and possibly beyond, will be incomplete if adequate attention is not given to the oral literature or traditions of the African people. Every knowledge-led development strategy of any nation must be built on a solid foundational core of an understanding of values. As Africans, to craft a better future, we need to understand the lessons of our past, and this is to be achieved by a reconsideration of the values and principles enshrined in the oral traditions of these communities and cultures. Keywords: Oral traditions, literature, human development, Africa.